Involvement of the Na+/Ca2+ Exchanger in the Automaticity of Guinea-Pig Pulmonary Vein Myocardium as Revealed by SEA0400 - Iyuki Namekata; Yayoi Tsuneoka; Akira Takahara; Hideaki Shimada; Takahiko Sugimoto; Kiyoshi Takeda; Midori Nagaharu; Koki Shigenobu; Toru Kawanishi; Hikaru Tanaka (Journal of Pharmacological Sciences, 2009)
Abstract.: We examined the involvement of the Na+/Ca2+ exchanger in the automaticity of the pulmonary vein myocardium with a specific inhibitor, SEA0400. Action potentials were recorded from the myocardial layer of isolated guinea-pig pulmonary vein preparations, and Ca2+ transients were recorded from the cardiomyocytes. Spontaneous electrical activity was observed in 17.7% of the preparations, which was inhibited by either SEA0400 or ryanodine. In quiescent preparations, ouabain induced electrical activity and spontaneous Ca2+ transients, which were inhibited by SEA0400, as well as ryanodine. These results provide pharmacological evidence that the Na+/Ca2+ exchanger underlies the automaticity of the pulmonary vein myocardium. Keywords:: pulmonary vein myocardium, Na+/Ca2+ exchanger, automaticity